Clinical characteristics and outcomes of heart failure with preserved, mildly reduced, and reduced ejection fraction: A 6-month follow-up study - Goran Adnan Rahman; Abdulkareem Abdulwahab Al-Othman (Medical Journal of Babylon, 2022)
Background and Objective: Heart failure is a major public health problem with 64.3 million people affected all over the world, and it is an important cause for hospital admission and mortality. The aim of this study is to assess the clinical characteristics, frequency of hospitalization, and outcomes of heart failure with preserved, mildly reduced, and reduced ejection fraction. Materials and Methods: This is a prospective study of 91 patients aged more than 18 years of both genders with clinical features of heart failure supported by transthoracic echocardiography, who had been admitted to the Coronary Care Unit of Hawler Teaching Hospital for the period from October 2019 to February 2021. Heart failure patients were classified into preserved, mildly reduced, and reduced ejection fraction according to the European Society of Cardiology guidelines 2021 for the diagnosis of heart failure. The hospital outcomes, echocardiographic variables, the frequency of hospitalization, and mortality over 6 months were compared. Results: Among the 91 patients, the majority were females 48 (52.7%), the male: female ratio is 1:1.1, and the majority had heart failure with preserved ejection fraction 68 (75%). Ischemic heart disease 27 (30%) accounts for the majority of heart failure with preserved ejection fraction. Hyperlipidemia 17 (18.9%), orthopnea 15 (16.7%), paroxysmal nocturnal dyspnea 15 (16.5%), cardiovascular hospitalization 13 (14.3%), and mortality 6 (6.6%) were higher in heart failure with reduced ejection fraction. Conclusion: The high frequency rate of ischemic heart disease was reported in heart failure with preserved ejection fraction. Cardiovascular hospitalization and mortality rate were higher among heart failure patients with reduced ejection fraction.